Two-Phase Analysis of A Helical Microchannel Heat Sink Using Nanofluids - Narrein, K.; Sivasankaran, S.; Ganesan, P. (Taylor & Francis, 2015)
A three-dimensional helical microchannel heat sink (HMCHS) model is developed to investigate the heat transfer characteristics using Al2O3-water-based nanofluid. The two-phase mixture model with modified effective thermal conductivity and viscosity equations is employed for solving the problem numerically. The model developed is validated by comparing the results of Nusselt number with available experimental and numerical data for a wide range of Reynolds number. The detailed results of the thermal field are reported for the effects of helix radius (0.15-0.30mm), pitch (0.5-2.0mm), number of turns (7-10), and aspect ratio (1.5-3.0). The analysis presents a unique fundamental insight into the complex secondary flow pattern in the channel due to curvature effects.